Environmentalism in South Africa, 1972-1992: an historical perspective - Steyn, Maria Sophia (University of the Free State, 1998)
The latter half of the twentieth century has seen an unprecedented growth in humankind's concern for the natural environment and its finite capability to absorb unchecked industrial and demographic growth. This concern was first and foremost a global phenomenon and led directly to the emergence of global environmentalism from the late 1960s onwards. A key component in the history of the global environmental movement was the initiatives taken by the United Nations (UN) aimed at getting the governments of the world involved in and committed to strategies to remedy widespread environmental degradation. To achieve this goal the UN convened what turned out to be the two watershed events in global environmentalism, namely the United Nations Conference on the Human Environment (UNCHE) in Stockholm in 1972 and the United Nations Conference on Environment and Development (UNCED) in Rio de Janeiro in 1992. The purpose of this study is to provide an account of the history of the environmental movement in South Africa and the country's participation in the global environmental movement between UNCHE in 1972 and UNCED in 1992. South Africa's position in the global environmental movement between 1972 and 1992 was dubious at best. Due to the government's domestic policy of apartheid, South Africa was isolated in the international political arena, which impacted negatively on the country's involvement in global environmentalism. With only limited participation allowed in global environmentalism, the South African environmental movement did not stay in touch with the important changes that occurred on an international level in that it failed to identify and address the paradigm shift towards sustainable development from 1987 onwards. Although isolated, South Africa did participate in some aspects of the global environmental movement, notably those that involved the conservation of fauna and flora, while the government proved less willing to participate in global initiatives which could possibly place restrictions on the economic development of the country. South African environmentalism developed differently from its counterparts in other countries between 1972 and 1992, owing to the limited participation of both governmental and non-governmental role-players in the global environmental movement, and because of the political situation within South Africa in the same period. Although the government and the environmental non-governmental organisations (ENGOs) responded to some aspects of the new environmental agenda that emerged alongside global environmentalism in the late 1960s, South African .environmentalism between 1972 and 1988 remained largely focused on the conservation of fauna and flora. Important new trends in the official administration of environmental affairs were addressed with the creation of a state department for environmental affairs and the adoption of general environmental legislation. However, in contrast to national movements elsewhere in the world, the South African environmental movement between 1972 and 1988 was characterised by its apolitical nature. The environment only became a political issue in South Africa from 1988 onwards with the founding of Earthlife Africa and like-minded ENGOs which linked the widespread environmental degradation in South Africa with the government's domestic policy of apartheid. Through their activities the new environmentalist ENGOs broadened the scope of the environmental agenda of South African environmentalism and opened the movement up to new role-players such as antiapartheid organisations, political parties and labour unions. However, despite these new developments between 1988 and 1992, by 1992 the South African environmental movement was still a long way from reversing the detrimental human impact on the natural environment. The developments in South African environmentalism between 1972 and 1992 were therefore but the first tentative steps towards improving the South African environment.

Gedurende die tweede helfte van die twintigste eeu het die mensdom se besorgdheid ongeëwenaard toegeneem ten opsigte van die bewaring van die natuur en . laasgenoemde se beperkte vermoë om ongekontroleerde industriële en demografiese groei te absorbeer. Hierdie besorgdheid was by uitstek 'n internasionale verskynsel en het vanaf die laat sestigerjare direk tot die opkoms van internasionale environmentalism ('n term waarvoor tot op hede nog geen aanvaarbare Afrikaanse vertaling ontwikkel is nie) aanleiding gegee. Die inisiatiewe wat deur die Verenigde Nasies (VN) geneem is om regerings wêreldwyd te betrek en te verbind tot strategieë om die wydverspreide omgewingsagteruitgang te stuit, maak 'n kernkomponent van die geskiedenis van die internasionale omgewingsbeweging uit. Ten einde hierdie doelwitte te bereik, het die VN twee konferensies belê, wat as waterskeidings vir internasionale environmentalism beskou kan word. Die United Nations Conference on the Human Environment (UNCHE) het in 1972 in Stockholm plaasgevind en die United Nations Conference on Environment and Development (UNCED) is in 1992 in Rio de Janeiro gehou. Met hierdie studie is ten doel gestelom die gekiedenis van die omgewingsbeweging in Suid-Afrika en dié land se deelname aan die internasionale omgewingsbeweging weer te gee, en wel vanaf 1972 (UNCHE) tot 1992 (UNCED). Tussen 1972 en 1992 was Suid-Afrika se posisie In die internasionale omgewingsbeweging twyfelagtig. Die land was as gevolg van sy regering se binnelandse beleid van apartheid geïsoleerd binne die internasionale politieke arena. Hierdie isolasie het negatief ingewerk op die land se betrokkenheid by internasionale environmentalism en die Suid-Afrikaanse omgewingsbeweging het nie in voeling gebly met die belangrike veranderings wat op internasionale gebied plaasgevind het nie, sodat dit misluk het om vanaf 1987 die paradigmaverskuiwing na volhoubare ontwikkeling te identifiseer en aan te spreek. Ten spyte van sy isolasie het Suid- Afrika wel aan sekere aspekte van die internasionale omgewingsbeweging deelgeneem - veral dié wat betrekking gehad het op die bewaring van fauna en flora. Die regering was daarteenoor minder gewillig om deel te neem aan internasionale inisiatiewe wat die moontlikheid kon inhou om beperkings op die ekonomiese ontwikkeling van Suid-Afrika te plaas. Suid-Afrikaanse environmentalism het tussen 1972 en 1992 verskillend van ekwivalente in ander lande ontwikkel as gevolg van die beperkte deelname van beide die regering en nieregerings-rolspelers in die internasionale omgewingsbeweging, asook as gevolg van die heersende politieke situasie in Suid-Afrika tydens hierdie periode. Alhoewel die regering én nieregerings-omgewingsorganisasies op sekere aspekte van die nuwe omgewingsagenda wat in die laat sestigerjare tesame met internasionale environmentalism opgekom het, gereageer het, het Suid-Afrikaanse environmentalism tussen 1972 en 1988 hoofsaaklik op die bewaring van fauna en flora gefokus gebly. Belangrike nuwe tendense in die amptelike administrasie van omgewingsake is aangespreek deur die skepping van 'n staatsdepartement vir omgewingsake, asook die goedkeuring van algemene omgewingswetgewing. In teenstelling met nasionale bewegings elders in die wêreld, was die Suid-Afrikaanse omgewingsbeweging tussen 1972 en 1988 a-polities van aard. Die omgewing het eers vanaf 1988 'n politieke vraagstuk in Suid-Afrika geword met die stigting van Earthlife Africa en soortgelyke nieregerings-omgewingsorganisasies, wat die wydverspreide omgewingsagteruitgang in Suid-Afrika aan die regering se binnelandse beleid van apartheid gekoppel het. Deur hul aktiwiteite het die nuwe environmentalist nieregerings-omgewingsorganisasies die veld wat die omgewingsagenda in Suid-Afrika gedek het, verbreed. Die beweging is ook oopgestel aan nuwe rolspelers, soos anti-apartheidsorganisasies, politieke partye en vakbonde. Ten spyte van hierdie nuwe verwikkelinge tussen 1988 en 1992, was die Suid- Afrikaanse omgewingsbeweging teen 1992 steeds ver daarvandaan om die nadelige menslike impak op die natuurlike omgewing te neutraliseer. Die ontwikkelinge in Suid-Afrikaanse environmentalism tussen die jare 1972 en 1992 was dus slegs die eerste, tentatiewe stappe wat geneem is ten einde die Suid-Afrikaanse omgewing te verbeter.
Dissertation (M.A. (History))--University of the Free State, 1998
Keywords: Environmentalism -- South Africa -- History, 20th century; Environmental management -- South Africa; Conservation of natural resources -- South Africa -- History, 20th century